STIBs interactive map facilitates bundling for women's empowerment and resilience - Alliance Bioversity and CIAT (Bioversity International and the International Center for Tropical Agriculture, 2023)
Socio-Technical Innovation Bundles (STIBs) are a combination or combinations of technological, technical, and social innovations co-designed to address women's empowerment and resilience (inclusive of men and youths).Non-STIBs combine only one or two types of innovations rather than all three. Here, we refer to bundles of only technological and technical, technical and social or technological and social bundles. Work package 2 EMPOWER of the CGIAR Initiative on Gender Equality (HER+) aims to identify, develop, and test context-specific STIBs to address climate change. The empower work package focuses on co-designing and testing partnerships and pathways to enhance uptake of climate smart STIBs by men, women, and youth. The goal of socio-technical innovations bundling is ultimately develop a toolbox that guides data, tools, and processes for creating, implementing, and evaluating climate-smart STIBs to empower women, men, youths and enhance their resilience. Thus, we have co-developed and co-designed a dashboard with an interactive map that dynamically displays the global distribution of socio-economic datasets, data, and tools that facilitate bundling in different local, regional, and thematic contexts.